Cross-Cultural Casting in Britain: The Path to Inclusion, 1972-2012 - Rogers, Jami (Multicultural Shakespeare: Translation, Appropriation and Performance, 2019)
This essay uses three productions to chart the progress of the integration of performers of African and Afro-Caribbean descent in professional British Shakespearean theatre. It argues that the three productions―from 1972, 1988 and 2012―each use cross-cultural casting in ways that illuminate the phases of inclusion for British performers of colour. Peter Coe’s 1972 The Black Macbeth was staged at a time when an implicit colour bar in Shakespeare was in place, but black performers were included in the production in ways that reinforced dominant racial stereotypes. Temba’s 1988 Romeo and Juliet used its Cuban setting to challenge stereotypes by presenting black actors in an environment that was meant to show them as “real human beings”. The RSC’s 2012 Julius Caesar was a black British staging of Shakespeare that allowed black actors to use their cultural heritages to claim Shakespeare, signalling the performers’ greater inclusion into British Shakespearean theatre.